Radiologic findings of screen-detected cancers in an organized population-based screening mammography program in Turkey - ÖZAYDIN, AYŞE NİLÜFER (AVES, 2016)
PURPOSE Bahcesehir Breast Cancer Screening Program is a population based organized screening program in Turkey, where asymptomatic women aged 40-69 years are screened biannually. In this prospective study, we aimed to determine the mammographic findings of screen-detected cancers and discuss the efficacy of breast cancer screening in a developing country. METHODS A total of 6912 women were screened in three rounds. The radiologic findings were grouped as mass, focal asymmetry, calcification, and architectural distortion. Masses were classified according to shape, border, and density. Calcifications were grouped according to morphology and distribution. Cancers were grouped according to the clinical stage. RESULTS Seventy cancers were detected with an incidence of 4.8/1000. Two cancers were detected in other centers and three were not visualized mammographically. Mammographic presentations of the remaining 65 cancers were mass (47.7%, n= 31), calcification (30.8%, n= 20), focal asymmetry (16.9%, n= 11), architectural distortion (3.1%, n= 2), and skin thickening (1.5%, n= 1). The numbers of stage 0, 1, 2, 3, and 4 cancers were 13 (20.0%), 34 (52.3%), 14 (21.5%), 3 (4.6%), and 1 (1.5%), respectively. The numbers of interval and missed cancers were 5 (7.4%) and 7 (10.3%), respectively. CONCLUSION A high incidence of early breast cancer has been detected. The incidence of missed and interval cancers did not show major differences from western screening trials. We believe that this study will pioneer implementation of efficient population-based mammographic screenings in developing countries.
Keywords: HORMONE REPLACEMENT THERAPY; BREAST-CANCER; WOMEN; TRIAL; CLASSIFICATION; SONOGRAPHY; CARCINOMA; ACCURACY; FEATURES; AGE